2007
DOI: 10.1038/sj.mp.4001994
|View full text |Cite
|
Sign up to set email alerts
|

Neuregulin1-induced cell migration is impaired in schizophrenia: association with neuregulin1 and catechol-o-methyltransferase gene polymorphisms

Abstract: Neuregulin1 (NRG1), a candidate susceptibility gene for schizophrenia, plays a critical role in neuronal migration and central nervous system development. However, its relation to schizophrenia pathogenesis is unknown. Here we show that B lymphoblasts migrate to NRG1 through the ErbB-signaling system as observed in neuronal cells. We assessed NRG1-induced cell migration in B lymphoblasts from patients with schizophrenia and found that NRG1-induced migration is significantly decreased compared with control indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
65
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(71 citation statements)
references
References 59 publications
6
65
0
Order By: Relevance
“…In schizophrenia, we propose that the increased expression of ErbB4 CYT-1 receptors and the increased fraction of CYT-1 to CYT-2 in the brain, combined with increased PIK3CD, create a molecular shift toward an attenuated NRG1-ErbB4-PI3K signaling system. This proposal is consistent with evidence showing impaired NRG1-mediated phosphorylation of AKT1 in patient-derived cells included in this study (53) and AKT1 dysfunction in schizophrenia (45,46). It is also noteworthy that reduced ErbB3 gene expression is observed in brain and LCLs of patients with schizophrenia (ref.…”
Section: Discussionsupporting
confidence: 76%
“…In schizophrenia, we propose that the increased expression of ErbB4 CYT-1 receptors and the increased fraction of CYT-1 to CYT-2 in the brain, combined with increased PIK3CD, create a molecular shift toward an attenuated NRG1-ErbB4-PI3K signaling system. This proposal is consistent with evidence showing impaired NRG1-mediated phosphorylation of AKT1 in patient-derived cells included in this study (53) and AKT1 dysfunction in schizophrenia (45,46). It is also noteworthy that reduced ErbB3 gene expression is observed in brain and LCLs of patients with schizophrenia (ref.…”
Section: Discussionsupporting
confidence: 76%
“…Consistent with basic models suggesting deficits in AKT phosphorylation and signaling underlying cognitive deficits (5, 7, 8), the A allele at rs1130233 associated with poorer cognitive func- tion and relative deficits in neuroimaging measures correspondingly evidenced reduced levels of AKT1 in the lymphoblasts of a subset of the same individuals (Figure 1). Thus, within the constraints of biological differences in the expression of physiological function between cell types, lymphoblasts potentially provide a useful model to test the functional status of genetic variation in the same living human subjects evaluated with neurocognitive tests and neuroimaging (65). This is exemplified here by genetically mediated differences in AKT1 protein abundance, assumed to reflect similar differences at the level of brain.…”
Section: Discussionmentioning
confidence: 95%
“…Epstein-Barr virus-transformed B lymphoblasts from a subgroup of 32 healthy controls (19 individuals with AKT1 SNP rs1130233 G/G and 13 individuals with A alleles) were prepared and AKT1 protein levels were analyzed by immunoblot (65). In brief, proteins extracted in buffer containing 250 mM Tris-HCl (pH 7.4), 100 mM NaCl, 1% Triton X-100, 0.1% SDS, 0.5% deoxycholic acid, 1 mM p-nitrophenylguanidinobenzoate, and protease inhibitor cocktails I and II (Sigma-Aldrich) were separated using SDS-PAGE on 4%-12% Tris-Glycine gel (Invitrogen).…”
Section: Methodsmentioning
confidence: 99%
“…In fact, it has been reported that NRG-1-induced cell migration resulting from ErbB-Akt signaling is impaired in immortalized lymphocyte from patients with schizophrenia. 32 Further studies are required to assess whether immortalized lymphocytes are a good tool to determine the effect of genetic risks on their gene expression and whether immortalized lymphocytes are an appropriate alternative to neuronal tissue. Dysbindin-1 and NRG-1 expression in lymphoblasts H Yamamori et al…”
Section: Discussionmentioning
confidence: 99%